Health-related quality of life in the randomised KEYNOTE-002 study of pembrolizumab versus chemotherapy in patients with ipilimumab-refractory melanoma. (November 2016) - Schadendorf, Dirk; Dummer, Reinhard; Hauschild, Axel; Robert, Caroline; Hamid, Omid; Daud, Adil; van den Eertwegh, Alfons; Cranmer, Lee; O'Day, Steven; Puzanov, Igor; Schachter, Jacob; Blank, Christian; et al.
Abstract: Background: In KEYNOTE-002, pembrolizumab significantly prolonged progression-free survival and was associated with a better safety profile compared with chemotherapy in patients with advanced melanoma that progressed after ipilimumab. We present health-related quality of life (HRQoL) outcomes from KEYNOTE-002. Methods: Patients were randomly assigned 1:1:1 to pembrolizumab 2 or 10 mg/kg every 3 weeks (Q3W) or investigator-choice chemotherapy. HRQoL was assessed using the European Organisation for Research and Treatment of Cancer Quality-of-Life Questionnaire-Core 30 instrument. A constrained longitudinal data analysis model was implemented to assess between-arm differences in HRQoL scores. The study is registered withClinicalTrials.gov, numberNCT01704287 . Results: Of the 540 patients enrolled, 520 were included in the HRQoL analysis. Baseline global health status (GHS) was similar across treatment arms. Compliance rates at week 12 were 76.6% ( n  = 108), 82.3% ( n  = 121), and 86.4% ( n  = 133) for the control, pembrolizumab 2 mg/kg Q3W, and pembrolizumab 10 mg/kg Q3W arms, respectively. From baseline to week 12, GHS/HRQoL scores were maintained to a higher degree in the pembrolizumab arms compared with the chemotherapy arm (decrease of −2.6 for each pembrolizumab arm versus −9.1 for chemotherapy; P  = 0.01 for each pembrolizumab arm versus chemotherapy). Fewer patients treated with pembrolizumab experienced deterioration in GHS at week 12 (31.8% for pembrolizumab 2 mg/kg, 26.6% for 10 mg/kg, and 38.3% for chemotherapy), with similar trends observed for the individual functioning and symptoms scales. Conclusions: HRQoL was better maintained with pembrolizumab than with chemotherapy in KEYNOTE-002, supporting the use of pembrolizumab in patients with ipilimumab-refractory melanoma. Highlights: Health-related quality of life (HRQoL) was evaluated in the KEYNOTE-002 study. HRQoL was maintained to a greater degree with pembrolizumab versus chemotherapy. In all arms, HRQoL decreased in patients who experienced disease progression. These data support pembrolizumab for ipilimumab-refractory advanced melanoma.